An ultrasound–negative pressure cavitation adsorption method for the recovery of paclitaxel from cell-free culture supernatants of Taxus chinensis - Kang, Yeji; Kim, Jin-Hyun (Biotechnology and bioprocess engineering, 2024)
In this study, an adsorption method using a synergistic effect between ultrasound and negative pressure cavitation was developed for the efficient recovery of paclitaxel from the culture supernatants of Taxus chinensis onto an adsorbent Diaion HP-20. The equilibrium adsorption data were matched to Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherms, and the Langmuir model was found to be the best fit. As the ultrasonic power and negative pressure intensity increased, the adsorption capacity and adsorption rate constant increased, and the intraparticle diffusion resistance sharply decreased. The combined ultrasound and negative pressure cavitation method achieved the best adsorption, and the synergistic effect was up to 65% at ultrasonic powers/negative pressure intensities of 80 W/–50 mmHg to 250 W/–200 mmHg. Paclitaxel adsorption onto Diaion HP-20 was endothermic and spontaneous. In addition, the isosteric heat of adsorption does not depend on surface loading, so the adsorbent has an energetically homogeneous surface.